Anomalies in the electrophysical, thermal, and elastic properties of layered ferroelectric semiconductor TlGaSe2 - Seyidov, M. -H. Yu.; Suleymanov, R. A. (Pleiades Publishing Inc, 2008)
The temperature dependences of the permittivity, dark current, and current-voltage characteristics of the layered ferroelectric semiconductor TlGaSe2 were measured over the range 77-300 K. The epsilon(T) curve measured perpendicular to the layers at low frequencies is discovered for the first time to exhibit an anomalous dip with clearly defined boundaries at similar to 150 and similar to 200 K. Electrical instability in the form of low-frequency oscillations of current in current-voltage characteristics of a sample in the same temperature range are also observed experimentally for the first time. It is shown that this instability occurs only if an electric field is applied to a sample using potential-controlling contactless electrodes in the form of thin mica spacer layers. The nature of the instability and its influence on various physical properties of the layered TlGaSe2 crystal are discussed.
Keywords: Phase-Transitions; Soft-Mode; Tlins2; Conductivity; Deformation; Anisotropy; Expansion; Crystals; Spectra; Light